Contrasting Mesozoic evolution across the boundary between on and off craton regions of the South African plateau inferred from apatite fission track and (U‐Th‐Sm)/He thermochronology. Issue 2 (25th February 2017) - Wildman, Mark; Brown, Roderick; Persano, Cristina; Beucher, Romain; Stuart, Finlay M.; Mackintosh, Vhairi; Gallagher, Kerry; Schwanethal, James; Carter, Andrew
Abstract: The timing and mechanisms involved in creating the elevated, low‐relief topography of the South African plateau remain unresolved. Here we constrain the thermal history of the Southwest African plateau since 300 Ma by using apatite fission track (AFT) and (U‐Th‐Sm)/He (AHe) thermochronology. Archean rocks from the center of the Kaapvaal Craton yield AFT ages of 331.0 ± 11.0 and 379.0 ± 23.0 Ma and mean track lengths (MTLs) of 11.9 ± 0.2 and 12.5 ± 0.3 µm. Toward the southwest margin of the craton and in the adjacent Paleozoic mobile belt, AFT ages are significantly younger and range from 58.9 ± 5.9 to 128.7 ± 6.3 Ma and have longer MTLs (>13 µm). The range of sample AHe ages complements the AFT ages, and single‐grain AHe ages for most samples are highly dispersed. Results from joint inverse modeling of these data reveal that the center of the craton has resided at near‐surface temperatures (<60°C) since 300 Ma, whereas the margins of the craton and the off‐craton mobile belt experienced two discrete episodes of cooling during the Cretaceous. An Early Cretaceous cooling episode is ascribed to regional denudation following continental breakup. Late Cretaceous cooling occurs regionally but is locally variable and may be a result of a complex interaction between mantle‐driven uplift and the tectonic setting of the craton margin. Across the entire plateau, samples are predicted to have remained at near‐surface temperatures throughout the Cenozoic, suggesting minimal denudation (<1 km) and relative tectonic stability of the plateau. Key Points: New AFT and AHe data reveal contrasts in the thermal history of on‐ and off‐craton regions during the Mesozoic Interior craton has stayed at less than 60 degrees Celsius since 300 Ma; off‐craton experienced two discrete episodes of cooling during the Cretaceous Late Cretaceous denudation focused along basement structures at the craton margin and is linked to the erosion of uplifted fault blocks